Review Article: Life Expectancy of Multiple Sclerosis in the US - Tariq, Dr Shabrez; Ahmed, Dr Areeb; Shamim, Dr Zainab (American Journal of Health, Medicine and Nursing Practice, 2024)
Purpose: Comprehending the life expectancy of individuals afflicted with MS is crucial for patient counseling and devising effective healthcare plans accordingly. Materials and Methods: In this review, we amalgamate findings from several key studies published between 2014 and 2024, using Scopus, Google Scholar, and PubMed to provide insight into the mortality and life expectancy associated with MS. Findings: Multiple sclerosis (MS) is a progressive, immune-mediated, neurodegenerative disease that incurs demyelination of the axons. MS impacts approximately 900,000 young adults in the United States, with an average onset age ranging from 20 to 30 years. MS population has been frequently associated with declining quality of life (QOL) as opposed to other chronic disease populations. Though, studies suggest physical impairment including weakness, gait disorders, or visual or emotional disturbances are pivotal determinants of life expectancy in MS patients. We will discuss each factor that influences the longevity of individuals with MS in detail below. Literature shows that 90% of cases with early disease experience relapses and remissions characteristically. While a small percentage of individuals follow a mostly benign course over an extended period, the majority establishes a secondary-progressive disease as soon as 6-7 years after the onset. Although a minor segment of MS manifests an "aggressive" disease, life expectancy is mostly unaffected with the disease course often prevailing over a period of 30 years on average, unless the patient’s comorbidities, compliance to treatment, or genetic predisposition are unfavourable. Implications to Theory, Practice and Policy: We aim to enhance understanding of this disease and its multifaceted aspects for advance management strategies, better quality of life hence improved patient outcomes.